S.O.S. Mathematics CyberBoard

Your Resource for mathematics help on the web!
 It is currently Sat, 3 Dec 2016 12:40:22 UTC

 All times are UTC [ DST ]

 Page 1 of 1 [ 3 posts ]
 Print view Previous topic | Next topic
Author Message
 Post subject: y""-y=u1(t)-u2(t)Posted: Thu, 3 Nov 2011 21:29:14 UTC
 S.O.S. Oldtimer

Joined: Fri, 30 Oct 2009 16:33:10 UTC
Posts: 261
Here is what I am given:

-y=u1(t)-u2(t); y(0)=0, y'(0)=0, y"(0)=0, y"'(0)=0

So here is what I tried:

L{}-L{y}=L{u1(t)}-L{u2(t)}

sL{y"'}-y"'-L{y}=L{u1(t)}-L{u2(t)}

s(sL{y"})-y"-L{y}=L{u1(t)}-L{u2(t)}

(sL{y'})-y'-L{y}=L{u1(t)}-L{u2(t)}

(sL{y})-y-L{y}=L{u1(t)}-L{u2(t)}

L{y}-L{y}=L{u1(t)}-L{u2(t)}

(-1)L(y)=L{u1(t)}-L{u2(t)}

Now my problem is that the problem didn't tell me a thing about u1 or u2 so I have no idea what to do with them.

Top

 Post subject: Re: y""-y=u1(t)-u2(t)Posted: Thu, 3 Nov 2011 21:33:14 UTC
 S.O.S. Oldtimer

Joined: Fri, 30 Oct 2009 16:33:10 UTC
Posts: 261
Oh boy, the first post doesn't look right at all. Hopefully this is a little easier to read:

y^(4)-y=u1(t)-u2(t); y(0)=0, y'(0)=0, y"(0)=0, y"'(0)=0

So here is what I tried:

L{y^(4)}-L{y}=L{u1(t)}-L{u2(t)}

sL{y"'}-y"'-L{y}=L{u1(t)}-L{u2(t)}

s(sL{y"})-y"-L{y}=L{u1(t)}-L{u2(t)}

s^{2}(sL{y'})-y'-L{y}=L{u1(t)}-L{u2(t)}

s^{3}(sL{y})-y-L{y}=L{u1(t)}-L{u2(t)}

s^{4}L{y}-L{y}=L{u1(t)}-L{u2(t)}

(s^{4}-1)L(y)=L{u1(t)}-L{u2(t)}

Now my problem is that the problem didn't tell me a thing about u1 or u2 so I have no idea what to do with them.

Top

 Post subject: Re: y""-y=u1(t)-u2(t)Posted: Fri, 4 Nov 2011 05:59:35 UTC
 Moderator

Joined: Wed, 30 Mar 2005 04:25:14 UTC
Posts: 15556
Location: Austin, TX
goteamusa wrote:
Oh boy, the first post doesn't look right at all. Hopefully this is a little easier to read:

y^(4)-y=u1(t)-u2(t); y(0)=0, y'(0)=0, y"(0)=0, y"'(0)=0

So here is what I tried:

L{y^(4)}-L{y}=L{u1(t)}-L{u2(t)}

sL{y"'}-y"'-L{y}=L{u1(t)}-L{u2(t)}

s(sL{y"})-y"-L{y}=L{u1(t)}-L{u2(t)}

s^{2}(sL{y'})-y'-L{y}=L{u1(t)}-L{u2(t)}

s^{3}(sL{y})-y-L{y}=L{u1(t)}-L{u2(t)}

s^{4}L{y}-L{y}=L{u1(t)}-L{u2(t)}

(s^{4}-1)L(y)=L{u1(t)}-L{u2(t)}

Now my problem is that the problem didn't tell me a thing about u1 or u2 so I have no idea what to do with them.

You cannot do too much about them, you just gotta write et cetera.

_________________
(\ /)
(O.o)
(> <)
This is Bunny. Copy Bunny into your signature to help him on his way to world domination

Top

 Display posts from previous: All posts1 day7 days2 weeks1 month3 months6 months1 year Sort by AuthorPost timeSubject AscendingDescending
 Page 1 of 1 [ 3 posts ]

 All times are UTC [ DST ]

Who is online

Users browsing this forum: skipjack

 You cannot post new topics in this forumYou cannot reply to topics in this forumYou cannot edit your posts in this forumYou cannot delete your posts in this forum

Search for:
 Jump to:  Select a forum ------------------ High School and College Mathematics    Algebra    Geometry and Trigonometry    Calculus    Matrix and Linear Algebra    Differential Equations    Probability and Statistics    Proposed Problems Applications    Physics, Chemistry, Engineering, etc.    Computer Science    Math for Business and Economics Advanced Mathematics    Foundations    Algebra and Number Theory    Analysis and Topology    Applied Mathematics    Other Topics in Advanced Mathematics Other Topics    Administrator Announcements    Comments and Suggestions for S.O.S. Math    Posting Math Formulas with LaTeX    Miscellaneous